Flavonoids as Antidiabetic Agents - Yana Cahyana; Tsani Adiyanti (Universitas Gadjah Mada, 2021)
Flavonoids are polyphenol compounds that exert many potential health benefits, including diabetes type-II, which is the third most common disease that causes death, right after cancer and cardiovascular diseases. The excessively high level of blood glucose has been believed to trigger type II diabetes. The aim of this review is to describe the flavonoid's ability as an alternative treatment for diabetes type-II patients. This paper addresses several aspects in which flavonoids may impart a pivotal role in starch digestion, such as the interaction of flavonoids with enzymes involved in starch hydrolysis, the role of flavonoids in inhibiting glucose absorption, as well as the interaction of flavonoids with starch to form a complex resistant to hydrolysis. Further studies, however, are suggested to extensively carry out, particularly the ones dealing with the intervention study using human volunteers to reveal the role of flavonoids in the real applications. The data on human intervention studies are still rare and can further be exploited using meta-analysis to have firmer results. Flavonoids in the food matrix are more realistic to perform to reveal the effect of interaction with other compounds, which may affect the mechanism of flavonoids interaction or their bioavailability.